Ten Considerations for Research Funders Seeking to Enhance Knowledge Exchange and the Impact of Marine Science on Policy and Practice - Cvitanovic, Christopher; Wyborn, Carina; Glenn, Evora; Kelly, Rachel; Louder, Elena; van Putten, Elizabeth I.; Bednarek, Angela (Frontiers in Marine Science, 2021)
Research funders can play an important role in supporting the integration of marine science into policy and practice to enable evidence-informed decision-making. However, to date, there is a paucity of guidance available to help research funders understand the specific actions they can take to support knowledge exchange among the researchers that they fund and relevant stakeholders, particularly within marine contexts. This Brief Research Report aims to begin to fill this gap through an in-depth case study of the Lenfest Ocean Program (LOP). Specifically, through qualitative interviews with 32 participants across eight LOP funded research projects (i.e., case studies) we sought to: (i) understand the types of impacts that have resulted from the LOP funded research, (ii) determine which activities undertaken by the LOP enabled funded research projects to achieve these impacts, and (iii) synthesize findings to articulate the core lessons that have emerged from our examination of these research projects. Results show that the concept of “research impact” is complex and can be interpreted in a number of ways including: (i) raising awareness of research among end-users, (ii) development and expansion of social networks, (iii) the provision of information to decision-makers, (iv) the development of decision-support tools, and (v) a direct contribution to policy change. We highlight the ways by which the LOP has supported the attainment of these impacts, as well as 10 general considerations that research funders should consider when seeking to enhance the impact of the research that they fund on marine policy and practice.